OQÍTÍWSHÍNÍǸ ORATORLÍQ HÁM SÓYLEW MÁDENIYATÍN RAWAJLANDÍRÍW JOLLARÍ - Kossheterova, A.J. (SCIENCE and SOCIETY, 2023)
The article are presented the content, theoretical foundations, and analysis of the concepts aimed at developing the teacher's eloquence and speech culture.